2014
DOI: 10.1002/pd.4512
|View full text |Cite
|
Sign up to set email alerts
|

Fetal diagnosis of testicular torsion: what shall we tell the parents?

Abstract: Prenatal diagnosis of unilateral testicular torsion is a coincidental rare finding. Because the twisted testicle cannot be salvaged, induced delivery and prompt surgery are not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…However, treatment of prenatal torsion is controversial. Most of the authors have reported that antenatal torsion represents an irreversible intrauterine phenomenon with a salvation rate of less than 5% and termination of pregnancy should be considered urgently after the diagnosis of acute cases [ 6 , 110 ]. Bilateral torsion is considered a true emergency due to the risk of an abnormality, indicating urgent surgery in the newborn [ 6 , 111 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, treatment of prenatal torsion is controversial. Most of the authors have reported that antenatal torsion represents an irreversible intrauterine phenomenon with a salvation rate of less than 5% and termination of pregnancy should be considered urgently after the diagnosis of acute cases [ 6 , 110 ]. Bilateral torsion is considered a true emergency due to the risk of an abnormality, indicating urgent surgery in the newborn [ 6 , 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, there is a trend of significant differences between prenatal findings and postnatal prevalence, as observed in the case of benign testicular tumors, cysts, and epididymal appendages or testicular microlithiasis [ 18 , 116 ]; absence of studies about more detailed structures such as the epididymis [ 124 ]; scarce and heterogeneous normative data [ 4 , 22 ]; and a lack of management of findings such as hydrocele or undescended testicles [ 27 , 55 ]. IUTT could be the main exception to this trend, with studies focused on its diagnosis and management [ 6 , 108 , 125 ]. There are several benefits of evaluation of the scrotum and internal structures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Testis torsiyonlu olgularda cerrahi operasyon esnasında karşı testisin fiksasyonu konusunda literatürde değişik bilgiler olmakla beraber genel eğilim karşı tarafın eksplorasyonu şeklin-dedir. Aynı şekilde orşidopeksi sonrasında atrofiye giden testislerde antisperm antikorlarının karşı testisin sperm üretimi üzerindeki olumsuz etkileri nedeniyle eksize edilmesi gerekliliği; ya da atrofik de olsa hormonal aktivitenin devam edeceği için yerinde bırakılması gerektiği hususunda literatürde de henüz bir fikir birliği oluşmamıştır (4,(15)(16)(17). Bu çalışmanın yapıldığı dönem; eğitim kliniği olmamızın ilk yılları olması ve kliniğimizdeki, uzmanların farklı merkezlerden uzmanlıklarını almaları nedeniyle ilk operasyonda karşı testisin fiksasyonu, geç dönemde atrofiye giden testisin eksizyonu veya çıkarılmaması konusunda hastaya yaklaşımlarda farklılıklar olabilmekteydi.…”
Section: Bulgularunclassified